Deficit in specific cognitive domains associated with dementia in Parkinson's disease. (November 2018) - Pal, Anita; Pegwal, Nishi; Kaur, Simran; Mehta, Nalin; Behari, Madhuri; Sharma, Ratna
Highlights: Domain specific cognitive disturbances are present in Parkinson's disease (PD). Intact executive, attention and memory domains characterise PD without dementia. Deficits in several cognitive domains characterise dementia in PD. Abstract: Impairment in different cognitive domains such as executive functions, language, memory and visuospatial skills occur frequently in Parkinson disease (PD) leading to significant disability and deterioration in quality of life. Heterogeneity of cognitive impairment enhances risk of developing dementia as disease progress. The objective is to explore the pattern of cognitive impairment with reference to the affected domains in PD with or without dementia relative to healthy controls. In this study, 110 PD patients and 26 healthy control were categorized into groups using Mini Mental State Examination and Clinical Dementia Rating scores as PD without dementia (PDND, n = 65; MMSE score >24; CDR = 0–1), PD with dementia (PDD, n = 45; MMSE score ≤24; CDR = 0.5–3) and healthy control (HC, n = 26; MMSE score >26; CDR = 0). Both Patients and controls underwent individual assessments of working memory, semantic memory, attention, language, executive functions, psychomotor and visuospatial skills and dementia using different cognitive function tests. Findings revealed lower scores of word memory, attention, psychomotor speed, visuospatial skills and executive functions in PDD compared to PDND. Interestingly, in PDD scores of picture memory, semantic memory and language functions were comparable with PDND. Compared to HC, PDND had no impairment in working memory, attention and executive functions, whereas PDD had lower scores in all the cognitive domains tested. Results indicate that the deficits in word memory, attention, psychomotor speed, visuospatial skills and executive functions distinguishes PDD from PDND. Impairment in specific cognitive domains may be a biomarker for predicting onset of dementia in Parkinson's disease.